Interacting with eHealth – Towards Grand Challenges for HCI - schraefel, mc; André, Paul; White, Ryen W.; Tan, Desney; Berners-Lee, Tim; Consolvo, Sunny; Jacobs, Robert; Kohane, Issac; Dantec, Christopher A La; Mamykina, Lena; Marsden, Gary; Szolovits, Peter; et al. (ACM SIGCHI Conference on Human Factors in Computing Systems (CHI 2009), Boston, U.S.A., 2009)
While health records are increasingly stored electronically, we, as citizens, have little access to this data about ourselves. We are not used to thinking of these official records either as ours or as useful to us. We increasingly turn to the Web, however, to query any ache, pain or health goal we may have before consulting with health care professionals. Likewise, for proactive health care such as nutrition or fitness, or to find fellow-sufferers for post diagnosis support, we turn to online resources. There is a potential disconnect between points at which professional and lay eHealth data and resources intersect for preventative or proactive health care. Such gaps in information sharing may have direct impact on practices we decide to take up, the care we seek, or the support professionals offer. In this panel, we consider several places within proactive, preventative health care in particular HCI has a role towards enhancing health knowledge discovery and health support interaction. Our goal is to demonstrate how now is the time for eHealth to come to the forefront of the HCI research agenda.